The Bacterial Symbiont Phaeobacter inhibens Shapes the Life History of Its Algal Host Emiliania huxleyi - Bramucci, Anna R.; Labeeuw, Leen; Orata, Fabini D.; Ryan, Elizabeth M.; Malmstrom, Rex R.; Case, Rebecca J. (Frontiers in Marine Science, 2018)
Marine microbes form host-associated biofilm communities that are shaped by complex interactions between bacteria and their host. The roseobacter Phaeobacter inhibens exploits both symbiotic and pathogenic niches while interacting with its microalgal host Emiliania huxleyi. During co-cultivation over extended periods with E. huxleyi, we show that P. inhibens selectively kills two host cell types, the diploid calcifying strain and the haploid flagellated strain. Meanwhile, various non-calcifying diploid strains are resistant to this pathogen or the pathogen is avirulent to this cell type. This differential pathogenesis has the potential of dramatically altering the composition of E. huxleyi blooms, which are typically dominated by the roseobacter-susceptible calcifying strain. This cell type makes calcite plates, which are an important sink in the marine carbon cycle and forms part of the marine paleobotanic record. P. inhibens kills the haploid cells, which have been proposed as critical to the survival of the algae, as they readily escape both eukaryotic predation and viral infection. Consequently, bacteria such as P. inhibens could influence E. huxleyi's life history by selective pathogenesis, thereby altering the composition of cell types within E. huxleyi populations and its bloom-bust lifestyle.